ANTARA JANJI DAN REALITA KRITIK SOSIAL DALAM PUISI ‘HENDAK KEMANA NEGRIKU’ KARYA ERI MIYARTO: ANALISIS NASIONALISME - Ifadatul Khusnah, Sofiana Aulia; Yunus, Syarifudin (Cahaya Ilmu Bangsa Institute, 2025)
Poetry, as a literary work, plays a crucial role in voicing social concerns and national spirit. This study analyzes the poem